New Methods of Teaching English (Eurasian Scientific Herald, 2022)
This article discusses how to teach English quickly and easily with the help of modern methods. These methods provide the lessons to be organized in a high mood which is really important for both learners and teacher. Also, it includes advice for young teachers to conduct the lessons lively as well as there are some clues for conducting learner-centered lessons.